Surgical Management of Left Sinus of Valsalva Aneurysm Presenting with Exertional Chest Pain - Ali Gurbuz; Sahin Iscan; Orhan Gokalp; Erturk Karaagac; Senem Girgin; Murat Aksun (Brazilian Journal of Cardiovascular Surgery, 2020)
Abstract Left sinus of Valsalva aneurysm (SVA) is a very infrequent clinical entity. Valsalva aneurysms are often asymptomatic in right and non-coronary sinuses and the diagnosis is often incidental. A left SVA which presents with exertional chest pain due to compression of left coronary system arteries is extremely rare. In this case, we present a successful surgical repair of left SVA without aortic regurgitation or myocardial infarction in a 59-year-old male patient.